(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Ensuring that primary school students have the opportunity to independently demonstrate their creative abilities, self-confidence in the classroom, independent decision-making in the performance of creative tasks, in order to effectively develop the creative activity, passion and interest of the primary school student and creating a creative environment is important.